1998
DOI: 10.1161/01.res.83.7.730
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial NADPH Oxidase as the Source of Oxidants in Lungs Exposed to Ischemia or High K +

Abstract: We have previously demonstrated the generation of reactive oxygen species (ROS) in cultured bovine pulmonary artery endothelial cells (BPAECs) and in isolated perfused rat lungs exposed to high K+ and during global lung ischemia. The present study evaluates the NADPH oxidase pathway as a source of ROS in these models. ROS production, detected by oxidation of the fluorophore, dichlorodihydrofluorescein, increased 2.5-fold in BPAECs and 6-fold in rat or mouse lungs exposed to high (24 mmol/L) K+. ROS generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
219
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(230 citation statements)
references
References 32 publications
(52 reference statements)
8
219
0
3
Order By: Relevance
“…These NOX's appear to control several vascular processes, such as vascular tone, vascular cell growth and angiogenesis, and inflammation. Accordingly, pulmonary endothelial cells have been demonstrated to generate NADPH-derived oxidants in response to pulmonary ischemia (178,179) as well as hyperoxia (180), which is associated with membrane depolarization due to the activation of K(ATP) channels, and resulting in stimulated endothelial cell proliferation and NO production (178,181,182). Although these responses were in some cases inhibited by catalase, suggesting the involvement of H 2 O 2 (182), recent studies also suggest a role for O 2 •− in endothelial NOX signaling (77).…”
Section: Functional Aspects Of Nox In Other Lung Cell Typesmentioning
confidence: 99%
“…These NOX's appear to control several vascular processes, such as vascular tone, vascular cell growth and angiogenesis, and inflammation. Accordingly, pulmonary endothelial cells have been demonstrated to generate NADPH-derived oxidants in response to pulmonary ischemia (178,179) as well as hyperoxia (180), which is associated with membrane depolarization due to the activation of K(ATP) channels, and resulting in stimulated endothelial cell proliferation and NO production (178,181,182). Although these responses were in some cases inhibited by catalase, suggesting the involvement of H 2 O 2 (182), recent studies also suggest a role for O 2 •− in endothelial NOX signaling (77).…”
Section: Functional Aspects Of Nox In Other Lung Cell Typesmentioning
confidence: 99%
“…This method has been widely used in flow cytometry, fluorescence microplate assays, or fluorescence microscopy (Silveira et al, 2003;Tada et al, 2004;Watanabe 1998). Originally, it has been assumed that DCF-fluorescence appears as a consequence of the formation of superoxide anion radicals or hydrogen peroxide ACCEPTED MANUSCRIPT A C C E P T E D M A N U S C R I P T 4 and, therefore, has been regarded as a measure for the generation of this reactive oxygen species (Al-Mehdi et al, 1998;Hempel et al, 1999;Kurose et al, 1997). (Warrington, PA, USA).…”
Section: Introductionmentioning
confidence: 99%
“…and H 2 O 2 , which may inactivate nitric oxide, may modulate redox-sensitive signaling pathways and gene expression, and are implicated in the pathophysiology of disorders such as hypercholesterolemia and atherosclerosis (1,2). A major source of ROS production in endothelial cells has recently been found to be a phagocyte-type NADPH oxidase (2)(3)(4)(5)(6)(7)(8). Several studies have suggested that, at a molecular level, the endothelial NADPH oxidase is analogous to the phagocyte NADPH oxidase complex in that all the main components of the phagocytic enzyme (i.e.…”
mentioning
confidence: 99%
“…Several studies have suggested that, at a molecular level, the endothelial NADPH oxidase is analogous to the phagocyte NADPH oxidase complex in that all the main components of the phagocytic enzyme (i.e. gp91 phox , p22 phox , p47 phox , p67 phox , and Rac1) are detectable at both mRNA and protein level in endothelial cells (5,(7)(8)(9)(10)(11)(12). Furthermore, we and others have shown that the endothelial cell p22 phox and gp91 phox cDNA sequences are highly (Ͼ90%) homologous to published neutrophil sequences (8,12).…”
mentioning
confidence: 99%